Methodology for Teaching Pedagogical Dispute in the System of Professional Teacher Training (Eurasian Journal of Learning and Academic Teaching, 2023)
The article presents the general characteristic of the model of teaching future teachers to the pedagogical dispute as a professionally significant statement, describes the course of the formation in students of special knowledge and skills associated with a comprehensive assessment of the situation of the dispute from the point of view of its genre parameters and modeling of effective and correct speech behavior in specific conditions of pedagogical interaction.